Relationship between systems and environment in the context of global-warming - Shankhi, Krishna P. (Journal of Agriculture and Environment, 2007)
Along with the change in the living standard of the people, science and technology based innovations have created many unwanted and detrimental consequences. Lacking the holistic and multi-perspective approach and ignoring the relationship between the systems and the environment have adversely affected our natural resources – soil, water and air to the extent of frequently occurring painful natural calamities and constantly increasing global warming. System Learning Approach, a systemic and holistic approach accommodates all these issues and these are reflected on the experiential learning process and hence there is little chance for wrong implementation. It is focussed on some livestock related environmental problems, particularly the methane gas emission from the ruminant animals and the ways to reduce it through green based feeding, increased productivity and their population control. It is also explored about the misuse of the land and the soil erosion and the way to improve the situation. The Journal of AGRICULTURE AND ENVIRONMENT Vol. 8, 2007, pp. 55-61